The Effect of Training on Employee Performance Mediated by Service Quality - Yusuf, Rr. Nurul Zulaekha; Sawitri, Dyah; Farhan, Djuni (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2021)
The bank plays an essential role in the Indonesian economy. Service quality and employee performance have become a priority for human development in Malang City. Therefore, this study will examine the effect of training on employee performance mediated by service quality. These study purposes are as follow: 1) knowing the effect of training on service quality of Bank Jatim in Malang Region, 2) knowing the effect of service quality on employee performance of Bank Jatim in Malang Region, 3) knowing the effect of service quality on employee performance of Bank Jatim in Malang Region, 4) knowing the effect of training on employee performance mediated by service quality of Bank Jatim in Malang Region. This is a survey research using an explanatory approach. The research location was Bank Jatim in Malang Region, which 48 respondents. Data was collected using a questionnaire and filled in by respondents. From the data obtained, mediation analysis is done to examine the effect of each variable. This research has four findings. First, training has a positive and significant effect on service quality. Second, training has a positive and significant effect on employee performance. Third, Service quality has a positive and significant effect on employee performance. Service quality mediates the effect of training on employee performance.